Efficacy of platelet rich plasma for acceleration of healing in chronic wounds; research article - Khan, Mujtuba Pervez; Hyder Ali; Suneel Kumar (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the standard dressing with normal saline with platelet-rich plasma for acceleration of healing in patients with chronic wounds. Method: The study was conducted at the Department of Plastic and Reconstructive Surgery, Dow University of Health Sciences and Dr K.M. Ruth Pfau Civil Hospital, Karachi, from April 1, 2019, to March 31, 2020, and comprised patients of either gender aged 18-60 years with arterial ulcers on the lower limb with dimension of wound <10cm2, haemoglobin >10g/dl and platelet count >150x109/L. The patients were randomised into control group A, which received conventional treatment of dressing with normal saline, and intervention group B, which received daily dressings with normal saline and weekly application of platelet-rich plasma. The procedure was repeated every week for 3 weeks. Bates Jensen wound assessment tool was used to assess the final outcome. Data was analysed using SPSS 20. Results: Of the 98 patients, with mean age 41.68±11.03 years, there were 49(50%) in group A; 45(91.8%) males and 4(8.2%) females with overall mean age 40.10±10.8 years. The other 49(50%) patients were in group B; 39(79.6%) males and 10(20.4%) females with overall mean age 43.27±11.1 years (p>0.05). Mean wound assessment score of group B patients decreased significantly compared to group A (p=0.002). Conclusion: Platelet-rich plasma treatment showed better performance in accelerating healing of chronic arterial wounds compared to the standard treatment of daily dressing with normal saline. Key Words: Wounds, Platelet-rich plasma.